HUBUNGAN PENILAIAN DIRI DENGAN PRESTASI BELAJAR MAHASISWA PENDIDIKAN DOKTER JENJANG PRE KLINIK ANGKATAN 2020 UNIVERSITAS UDAYANA - Setyawan, I Wayan Gede Adi Febrian; Sundariyati, I Gusti Ayu Harry; Darmayanti, I Gusti Ayu Sri; Ganesha, I Gde Haryo (Universitas Udayana, 2023)
Self-assessment is an important component in the self-development of a student or clinician. Self-assessment clarifies learning objectives, monitors the learning process and conducts self-reflection. This study aims to analyze the relationship between self-assessment and learning achievement of pre-clinical medical student udayana university batch 2020. This study used an analytical method (cross-sectional). A sample of 165 students of pre clinical medical student udayana university batch 2020 participated in this study. The self-assessment data was obtained using a questionnaire of 12 items that were valid and reliable (0.770>0.600). Meanwhile, student achievement data uses MCQ scores on the Clinical Nutrition and Disorders exam. Analysis of the relationship between self-assessment and student achievement using Spearman correlation with a significance degree of 95% (p<0.05). The results show that there is no significant relationship between self-assessment and learning achievement of pre clinical medical student udayana university batch 2020 with the value of Sig. (2-tailed) was 0.666 (>0.05). Self-assessment of learning does not correlate with student achievement. Keywords: Self-assessment, learning achievement, medical education.